The Body Condition Score of Pigs Infected With Gastrointestinal Parasites In Dogiyai District, Papua Province, Indonesia - Yosea Dou; Noviyanti Noviyanti; Priyo Sambodo (Journal of Applied Veterinary Science And Technology, 2023)
Background: Pigs are a mainstay of traditional husbandry in Papua, and people in Dogiyai Regency determine the selling price of pigs through physical appearance. Severe worm parasite infestations will affect the health status of the livestock, which hypothetically would affect the body condition score (BCS). Purpose: This study examined the association between gastrointestinal worm infection and pigs' body condition scores (BCSs) in Dogiyai Regency, Papua Province, Indonesia. Methods: Interviews and direct observations were conducted among farmers in Dogiyai Regency. Stool samples were collected from pigs and examined using native and quantitative methods. BCSs were assessed by observing the appearance of adult pigs. Data were analyzed using a descriptive method and presented in a tabulated format. Results: Most respondents had formal education and relatively high farming experience levels. They used the traditional farming system. Regarding morphology, the worm eggs identified were the strongyle type (36.12%), Strongyloides ransomi (26.48%), Oesophagostomum species (20.44%), and Trichuris suis (16.96%). Of the pigs, 91.11% had multiple infections at the following degrees of severity according to the number of eggs per gram (EPG): mild: 11.11%; moderate: 72.22%; and severe: 16.67%. The pigs with mild, moderate, and severe infections had BCSs ranging from 2 to 5, 1 to 5, and 3 to 4, respectively. Conclusion: In this study, gastrointestinal worm infection did not affect the BCSs of the pigs.